The Dravidian languages - Krishnamurti, Bhadriraju (Cambridge language surveys., 2003)
The Dravidian languages are spoken by nearly 200 million people in South Asia and in Diaspora communities around the world; they include Tamil, Malayalam, Kannada and Telugu. This book provides a linguistic overview of the Dravidian language family, including its history and writing systems, language structures, typology and lexicon.